2013
DOI: 10.1073/pnas.1304839110
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation regulates the SNF1 protein kinase

Abstract: The AMP-activated protein kinase (AMPK) is a major stress sensor of mammalian cells. AMPK's homolog in the yeast Saccharomyces cerevisiae, the SNF1 protein kinase, is a central regulator of carbon metabolism that inhibits the Snf3/Rgt2-Rgt1 glucose sensing pathway and activates genes involved in respiration. We present evidence that glucose induces modification of the Snf1 catalytic subunt of SNF1 with the small ubiquitin-like modifier protein SUMO, catalyzed by the SUMO (E3) ligase Mms21. Our results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 72 publications
1
59
0
Order By: Relevance
“…Previous evidence suggested that Snf1 can be SUMOylated, which promotes the conjugation of ubiquitin for degradation. This may in turn cause a decrease of Snf1 activity (18,21). Our current findings reveal a novel layer of regulation of Snf1 activity, involving a feedback loop between Snf1 protein level and its phosphorylation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Previous evidence suggested that Snf1 can be SUMOylated, which promotes the conjugation of ubiquitin for degradation. This may in turn cause a decrease of Snf1 activity (18,21). Our current findings reveal a novel layer of regulation of Snf1 activity, involving a feedback loop between Snf1 protein level and its phosphorylation.…”
Section: Discussionmentioning
confidence: 63%
“…SUMOylation can also regulate the stability and function of Snf1 (21). To examine the role of ubiquitylation in the reduction of Snf1 in ubp8⌬ ubp10⌬, we mutated the SUMOylation site (K549R) to inhibit SUMOylation-mediated recruitment of E3 ubiquitin ligases and subsequent degradation of Snf1.…”
Section: Level Of Snf1 Protein Is Altered By Deletion Of Ubp8 and Ubpmentioning
confidence: 99%
See 1 more Smart Citation
“…Also conserved is acetylation and ubiquitination, recently reported for both mammalian AMPK and yeast SNF1 kinase complexes (23)(24)(25)(26), that appear to have inhibitory roles in regulation of the kinase. Similarly, SUMOylation has been shown to be a negative regulator of Snf1 (27), clearly adding to the complexity of regulation of this central energy-sensing switch.…”
mentioning
confidence: 99%
“…Finally, most recently and remarkably, Simpson-Lavy and Johnston (Simpson-Lavy and Johnston, 2013) have demonstrated that the yeast Nse2 homolog, Mms21, can sumoylate the SNF1 protein, which is the yeast homolog of mammalian AMPactivated protein kinase (AMPK), thereby inhibiting its catalytic activity. In mammalian skeletal muscle cells, AMPK is a central player in the regulation of cell metabolism and fiber type specification, and skNAC has been implicated in the control of fiber type specification (Yotov and St-Arnaud, 1996;Park et al, 2010) (J.B. and B.M, unpublished data), suggesting that there is an interesting link between Nse2/Mms21 and skeletal muscle plasticity.…”
Section: Discussionmentioning
confidence: 99%